GRAPHIC ORIENTED DESIGN OF A MODERN CITY - Hovhannisyan, S. V. (Art and Design, 2021)
The purpose is to analyse the objects of graphic design from the position of their aesthetic expressiveness and effectiveness of perception in the process of human orientation in the space of a modern city. The research methodology is based on the complex use of historical and comparative methods, system analysis, synthesis, generalization. The specifics of the study of the sign as an object of graphic design involves the use of semantic analysis methods. The result reveal the historical aspects of the emergence and current trends in graphic communication signs and messages used to orient a person in the modern urban space. The communication messages of modern city inscriptions-names of objects, object-spatial and plane signs of orientation in the urban environment, road signs using graphic elements and fonts have been analyzed. The main features contributing to the effectiveness of the message and current trends of graphic means in solving the problems of orientation and communication in space are highlighted. The ways of using graphic signs to solve the tasks of orientation and communication taking into account, modern trends in socio-cultural space have been analyzed and systematized. The methods for transforming the graphic form of the sign, its functional tasks in the process of human interaction with the urban environment are considered. The analysis of graphic signs from the position of their application to solve navigation and, consequently, communication problems of the city, defines the specifics of further development of graphic design in the conditions of accelerated information and technological transformation of society, and actualizes the increasing number of visual ways to transmit information. The results of the study can be used as the information basis for the development of communication design objects in the space of the city.